Disrupción endocrina en peces (2012)
ABSTRACT: The exposure ofüving creatures to endocrine disruptors is universal, as they are scattered throughout the world as a resutí of its widespread use. The variety of endocrine disruptors is very broad and growing every day, including chemicals synthesized by humans, additionally to substances found naturaüy in the environment. The endocrine disruptors constitute a threat not only to animal healíh and reproduction, but possibly to humans as welL Biomarkers are used as risk indicators for endocrine disruption. Considered amongst them are plasma steroids levéis, induction of viteüogenin and zone radíate protein, and, histology and immunohistochemistry of the liver, gonads and other organs. The appropriate and combined use of biomarkers has allowed significant advances to understand fish reproductive toxicology in both field and laboratory studies. Given that few reports have been published in Colombia on this área, and considering its global importance, this article scrutinizes the state of the art on problems caused by the DE and points out the need of doing more research on this issue.